Running scared - Williamson, Joshua (DC Universe rebirth., 2017)
"The aftermath of "The Button" has left Barry Allen--the Fastest Man Alive, known as the Flash--at a crossroads. Can he continue lying to the woman he loves about his secret identity? Can he mend his broken relationship with Kid Flash? Green Lantern Hal Jordan offers some advice, but Flash doesn't have much time to make a decision, courtesy of the return of his greatest enemy, the time-traveling Reverse-Flash! Eobard Thawne has taken Iris West to the 25th century to reveal Barry Allen's most closely guarded secrets to her...before killing Iris and the Flash! Following them to the future, Flash finally learns why his arch-foe from the future hates him so much, but even that knowledge may not be enough to give him a fighting chance against a villain who knows all his possible futures."--